Approaches for numerical analysis and experimental monitoring of manufacturing process and damage evolution in carbon/titanium hybrid structures - Ghiavsand, S.; Airoldi, A.; Bettini, P.; Capizzi, G.M.; Bogotto, P. (My University, 2019)
The prediction of detailed mechanical respond in bonded Composite/Metal hybrid structure is hardly detectable due to the presents of thermal strain that depends on mismatch of Coefficient of Thermal Expansion (CTE), adhesive behavior, development of defects in adhesive layer during manufacturing or operational loads. These uncertainties could be overcome by optical fibre based monitoring systems and by a precise characterization of the manufacturing effects and damage progression on the stress-strain field. This paper presents a well-assessed monitoring technique based on strain sensors carried by optical fibers embedded in the hybrid specimen that can be used both during manufacturing process and fracture test to validate a numerical modelling approach for prediction of strain evolution. The experimental tests are conducted with two pre-damaged configurations, Balanced and Un-Balanced specimens equipped by two types of fiber coating, Naked fiber and Ormocer, to investigate the effects of thermal stress build-up on the fracture behavior. The hybrid specimens have been designed by the method that is capable of controlling thermal stress build-up. These specimens have been obtained by co-bonded process and have been suited for the Double cantilever Beam (DCB) fracture mechanic test. Validated numerical approach based on multistep explicit analyses have been used to implement the effect of thermal stress produced in the manufacturing on the simulation of fracture propagation.